Masalah Defisit Transaksi Berjalan Dalam Neraca Pembayaran Indonesia - Edalmen (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 1998)
A country’s balance of payment has two main parts, i.e. the current account and the capital account. The current account covers imports and exports of goods and services. While the capital account is money lent or invested abroad. By definition, the balance of payment must be in balance. A country with a 1 billion deficit on its current account must get 1 billion in foreign currency to finance it. This paper explains the deficit current account on Indonesia’s balance of payment.